Perceived cross-linguistic distance and exploitation of affordances provided by different levels of real formal and semantic similarity between languages - Letica Krevelj, Stela (Array, 2012)
The author will present a study that investigates cross-language interaction in trlinguals' production. It builds empirically on the widely acknowledged phenomenon that perceived cross-linguistic distance has an effect on the transferability of linguistic features from one language to another. More specifically, the study focuses on the effect of perceived cross-linguistic distance on noticing and capitalizing on the affordances provided by different levels of formal and semantic similarity between L1 and L3 and L2 and L3 during a word retrieval task in L3. Participants in the study were 50 Croatian-Italian-English trilinguals, high-school students with comparable age of onset, degree of exposure and levels of proficiency in all three languages. Apart from the questionnaire which elicited perceived distance between the three typologically unrelated languages the participants were given a paper and pencil test in which they were asked to read a list of sentences in English (their L3) and to supply a synonym for an underlined word in each sentence. The required synonymous words were slightly above the participants' level of knowledge in order to trigger cross-language interaction. The synonyms were manipulated in terms of levels of formal and semantic similarity with the words in either L1 or L2. The findings support the hypothesis that perceived linguistic distance has an effect on the cross-linguistic interactions, and offer additional insight into the nature of that influence across the types of real formal and semantic similarity present in each lexical item.